Electronic determination of root canal length in primary teeth with and without root resorption - Mente, Johannes; Seidel, Joachim; Buchalla, W.; Koch, Martin Jean (International endodontic journal, 2002)
To test an electrical device for determining root canal length in primary teeth in vitro, and to compare it with the radiographic length measurement.